DIGITAL TECHNOLOGY LEARNING FROM (2020-2025): A BIBLIOMETRIC ANALYSIS - Janney, Ezaidzul; Abdullah, Mohd Khairuddin (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This bibliometric analysis examines the global development of digital technology in learning from 2020 to 2025, emphasizing its impact on educational progress and the enhancement of teacher competency. Data comprising 39,827 documents including journal articles, conference proceedings, book chapters, and books were collected from the Scopus database. The information was analyzed using VOSviewer software version 1.6.15 to map networks of co-authorship, keyword relationships, and international research collaborations. The findings indicate a continuous increase in research output from 2020 to 2024, peaking with over 9,800 publications. Journal articles (46.7%) and conference papers (39.5%) were identified as the main mediums for research dissemination, supported by contributions from books and chapters offering deeper theoretical insights. Cluster analysis revealed five major research domains: technological advancement, sustainability, digital pedagogy, human-centered approaches, and engineering-related applications, highlighting the multidisciplinary nature of this field. Moreover, the visualization network showed that China, the United Kingdom, and the United States were the leading contributors to global collaboration, while countries such as Malaysia and Saudi Arabia demonstrated growing regional engagement. Overall, the study underscores the increasing importance of digital technology in transforming teaching and learning practices worldwide. It provides valuable insights into how technological integration strengthens professional development, fosters international collaboration, and supports the creation of equitable and future-ready education systems.